1985
DOI: 10.1007/bf02388611
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal aspiration syndrome due to vernix caseosa

Abstract: Fetal aspiration of meconium in amniotic fluid is a well-known cause of respiratory distress in newborn infants. It causes an irregular, coarse, nodular pattern on chest radiographs. Less known is that aspiration of vernix caseosa causes a similar syndrome. We present a post-mature infant in whom aspiration of vernix caseosa caused respiratory distress, ventilatory difficulty, and radiographic changes essentially the same as in aspiration of meconium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…2 The clinical presentation and radiological changes seen in this case suggest that, when inhaled, maternal blood produces similar effects to other particulate or toxic matter such as meconium, vernix and cellular debris. [2][3][4] Pulmonary haemorrhage is an important differential diagnosis but clinical and radiological features are quite distinct. 7 It is usually associated with severe respiratory compromise, efflux of haemorrhage fluid from the airways, post-haemorrhagic coagulopathy and thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The clinical presentation and radiological changes seen in this case suggest that, when inhaled, maternal blood produces similar effects to other particulate or toxic matter such as meconium, vernix and cellular debris. [2][3][4] Pulmonary haemorrhage is an important differential diagnosis but clinical and radiological features are quite distinct. 7 It is usually associated with severe respiratory compromise, efflux of haemorrhage fluid from the airways, post-haemorrhagic coagulopathy and thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…1 Respiratory distress in the newborn infant can occur owing to aspiration of a variety of amniotic fluid contaminants such as meconium, vernix caseosa and cellular debris. [2][3][4] It is suggested that aspiration of blood or blood-stained amniotic fluid could also cause aspiration syndrome in neonates. 1,5 However, very few cases have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Vernix caseosa has been implicated in the causation of neonatal aspiration syndrome8283 and vernix caseo-granulomatous meningitis 84. Hence, pregnant women with a diffuse pattern of high-level echoes in prenatal ultrasonography, suggesting the presence of massive vernix caseosa, should be shifted to a well-equipped institution for delivery.…”
Section: Diagnostic and Prognostic Implications Of Vernix Caseosamentioning
confidence: 99%
“…Only one case with vernix caseosa aspiration syndrome has been reported previously [3] . In that case, the male infant was born vaginally at 41 weeks of gestation with Apgar scores of 2 and 7 at 1 and 5 min, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Only one aspiration syndrome caused by an airway obstruction of vernix caseosa has been previously reported [3] . In that case, the infant's life was saved with intensive care.…”
Section: Introductionmentioning
confidence: 99%